Peranan Nilai-nilai Pangadereng Bugis Bone Terhadap Peningkatan akhlak Siswa Sekolah Menengah Umum di Watampone - Harnida, Harnida (Institut Agama Islam Negeri (IAIN) Bone, 2020)
This article examines the role of the values of the Bugis Bone Pangadereng to improve secondary school students in Watampone. This research includes field research using qualitative approaches. Data sources come from informers consisting of teachers and students as a primary data source and other supporting data in the form of other supporting documents. The Data that has been collected from the field is processed with qualitative descriptive techniques. The process of processing through three phases is data reduction, data presentation, and verification or withdrawal of sympulsion. The Data is either derived from the results of observation, interview or interview in depth, as well as from documented documents. The results showed that the method used by the teachers in implementing the values of the Bugis Bone Pangadereng to the improvement of students are: methods of Coaching, habituation methods, exemplary methods, advice methods, methods of giving attention and supervision, and methods of appreciation and punishment.As for the barriers and challenges in the application of the values of a Bugis Bone Pangadereng (1) The factor of the students themselves because a small part of the students have not understood the values of the Pangadereng itself, and they seemed to ignore this, caused by the development of the Times and the flow of information that led to the inclusion of culture from the outside, (2) The factor that comes from the teacher itself is the lack of awareness of the teacher in applying the values of the Pangadereng itself namely Sipakor , Sipakalebbi, and Mappatabe, (3) The factor of the students ' parents themselves, because there are some parents who only fully surrender their children's education in school.The role of the the values of Bugis Bone Pangadereng can increase the school students in Watampone because culture teaches the values of ethics that refers to the morality and moral goodness such as culture of courtesy, reverence, respect, and maintain self-esteem, Pangadereng also forms a more humble child and forms a more religious child